The effect of muscle damage on strength and fatigue deficits - Behm, D. G.; Baker, K. M.; Kelland, R.; Lomond, J. (The Journal of Strength and Conditioning Research, 2001)
Many studies have reported prolonged force deficits after a bout of resistance training. However there is a dearth of information on the neuromuscular mechanisms underlying these deficits. This study examined whether an acute bout of resistance training had prolonged detrimental effects on muscle activation and excitation-contraction coupling. Two groups of 16 subjects each were tested before resistance exercise and at 1, 3, 5, and 7 days postexercise. A dynamic group was tested for concentric and eccentric 1 repetition maximum and 3-methylhistidine (3-MH). An isometric group was tested for maximal voluntary contraction, muscle inactivation, relative fatigue, and evoked twitch properties. Both groups experienced similar increases in pain, limb circumference, and decreased range of motion between 1 and 3 days postexercise. Decrements occurred with eccentric strength, maximal voluntary contraction, muscle inactivation, relative fatigue, twitch amplitude, and increases in 3-MH. Although muscle damage-induced characteristics (pain, swelling, range of motion, 3-MH) were not correlated with neuromuscular impairments (muscle activation, force output), disruption of excitation-contraction coupling may have contributed to decrements in fatigue.